4-1BBL-Armed Oncolytic Herpes Simplex Virus Exerts Antitumor Effects in Pancreatic Ductal Adenocarcinoma - Wenrui Gao; Zhuoqian Zhao; Ying Bi; Jinghua Li; Na Tian; Cuizhu Zhang; Shuyuan Pan; Li Deng; Yuntao Zhang (Vaccines)
Background: Pancreatic ductal adenocarcinoma (PDAC) is a highly malignant tumor with a notably poor response to therapy due to its immunosuppressive tumor microenvironment (TME) and intrinsic drug resistance. The oncolytic virus (OV) represents a promising therapeutic strategy capable of transforming the “cold” immunological profile of PDAC tumors to a “hot” one by reshaping the TME. 4-1BB (CD137), a crucial member of the tumor necrosis factor receptor superfamily, plays a significant role in T-cell activation and function. Methods: In this study, we constructed an oncolytic herpes simplex virus armed with 4-1BBL (oHSV-4-1BBL), the ligand for the 4-1BB receptor, and investigated its therapeutic effects in two mouse models of pancreatic cancer, Pan02_HVEM and KPC. Results: We found that oHSV-4-1BBL remarkably inhibited tumor growth and extended the median survival time in both models. To amplify the therapeutic effect, we further combined oHSV-4-1BBL with PD-1 antibody. This combination therapy not only further suppressed tumor growth but also extended the median survival time by an additional 11 days compared to oHSV (armed with GFP as a control) combined with PD-1 antibody treatment, with some mice achieving complete tumor regression. Conclusions: Our findings confirm the potential of combining oncolytic viral therapy with 4-1BB targeting in enhancing the treatment of pancreatic cancer.